ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN - Intang, Mas; Radjab, Enny; Amin, Amelia Rezky (COMPETITIVENESS, 2020)
This study aims to analyze financial ratios to predict profit growth in banking companies listed on the Indonesia Stock Exchange. Research samples taken from members of the population are 10 banking companies listed on the Indonesia Stock Exchange. Data processing uses multiple linear regression and from the results of data processing and hypothesis testing, 1 (one) hypothesis is accepted, and 7 (seven) hypotheses are rejected. The conclusion in this study is that the liquidity ratio (Critical Ratio) and the liquidity ratio (Quick Ratio) do not have a significant effect on predicting profit growth, the activity ratio (Total Asset Turnover) and the activity ratio (Fixed Asset Turnover) do not have a significant effect on predicting profit growth. solvency (Debt to Equity Ratio) has no significant effect on predicting earnings growth and the solvency ratio (Debt Ratio) has a significant effect on predicting profit growth in banking companies listed on the IDX. The profitability ratio (Return on Assets) and the profitability ratio (Net Profit Margin) have no significant effect on predicting profit growth in banking companies listed on the IDX.Keywords: Liquidity Ratio, Activity Ratio, Solvency Ratio, Profitability Ratio